1992
DOI: 10.1007/bf00182995
|View full text |Cite
|
Sign up to set email alerts
|

Femoral shaft fractures after cemented total hip arthroplasty

Abstract: Thirty-seven femoral shaft fractures occurred in 2360 cemented hip arthroplasties carried out between 1971 and 1989 at varying intervals after operation (average 3.7 years). Three types of fracture were recognised and treatment depended on the type, as did the prognosis. Good results were obtained in 70% of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 13 publications
1
12
0
2
Order By: Relevance
“…[34][35][36][37][38][39][40] In the present study, the prevalence of periprosthetic fracture was 2 of 35 hips (5.7%), and the fractures occurred around 2 cementless femoral stems. No periprosthetic fracture occurred around the cemented femoral stems.…”
Section: Limitationsmentioning
confidence: 78%
“…[34][35][36][37][38][39][40] In the present study, the prevalence of periprosthetic fracture was 2 of 35 hips (5.7%), and the fractures occurred around 2 cementless femoral stems. No periprosthetic fracture occurred around the cemented femoral stems.…”
Section: Limitationsmentioning
confidence: 78%
“…Clinical studies, however, have shown that cerclage fixation alone is not rigid enough, and that it should be supplemented with other methods of internal fixation (Garcia-Cimbrelo et al 1992). DCPs can be fixed around a stable stem with unicortical screws, with or without cerclage wires or cables, and with bicortical screws below it.…”
Section: Discussionmentioning
confidence: 99%
“…Jed nym z nich są zła ma nia oko ło pro te zowe ko ści udo wej sta no wią ce, we dług szwedz kie go naro do we go re je stru pro tez sta wu bio dro we go z 2010 r., trze cią co do czę sto ści wy stę po wa nia przy czy nę opera cji re wi zyj nych po alo pla sty kach sta wu bio dro wego (9,5%), po asep tycz nym ob lu zo wa niu wsz cze pu (60,1%) i na wra ca ją cych zwi ch nię ciach pro te zy (13,1%) [2,3]. Czę stość wy stę po wa nia zła mań około pro te zo wych wy no si 1% -3% po alo pla sty kach cał ko wi tych ce men to wa nych [4], 3% -7% po bez cemen to wych [5] oraz 2,1% po ope ra cjach re wi zyjnych [3]. Czyn ni ka mi pre dys po nu ją cy mi do ich wystą pie nia są m.in.…”
Section: Wstępunclassified
“…Complications from hip replacement procedures include periprosthetic femoral fractures, which according to the Swedish Hip Arthroplasty Register of 2010, are the third most common cause of revision surgeries after hip arthroplasty (9.5%), following aseptic implant loosening (60.1%) and recurrent prosthesis dislocation (13.1%) [2,3]. Periprosthetic fractures occur in 1-3% of patients after total cemented hip replacement [4], 3-7% of those after cementless arthroplasty [5], and 2.1% of patients after revision surgeries [3]. Predisposing factors include osteoporosis, past surgery of the proxi mal femur (bone screw holes, deformation), periprosthetic osteolysis secondary to implant loosening, and internal and neurological co-morbidities which predispose patients to falls from standing height [6].…”
Section: Introductionmentioning
confidence: 99%